Put Me in the Game Coach! Resident Participation in High-Risk Surgery in the era of Big Data - Cobb, Adrienne N. (J Surg Res, 2018)
BACKGROUND: With the emphasis on quality metrics guiding reimbursement, concerns have emerged regarding resident participation in patient care. This study aimed to evaluate whether resident participation in high-risk elective general surgery procedures is safe. MATERIALS AND METHODS: The American College of Surgeons NSQIP database (2005-2012) was used to identify patients undergoing one of five high-risk general surgery procedures. Resident and non-resident groups groups were created using a 2:1 propensity score match. Postoperative outcomes were calculated using univariate statistics and multivariable logistic regression for the two groups. Predictors of mortality and morbidity were identified using machine learning in the form of decision trees. RESULTS: 25,363 patients met our inclusion criteria. Following matching, each group contained 500 patients and were comparable for matched characteristics. 30-Day mortality was similar between the groups (2.4% v. 2.6% p=0.839). Deep surgical site infection (0% v. 1.6% p=0.005), urinary tract infection (5% v. 2.5% p=0.029), and operative time (275.6 min v.250 min p=0.0064) were significantly higher with resident participation. Resident participation was not predictive of mortality or complications; while age, ASA class, and functional status were leading predictors of both. CONCLUSIONS: Despite growing time constraints and pressure to perform, surgical resident participation remains safe. Residents should be given active roles in the operating room, even in the most challenging cases.